Plagues of modernization and praise to patriarchate in Svetozar Marković’ “Serbia in the East” - Milosavljević, Ljubinko (Sociološki pregled, 2026)
In this paper, the author first gives a short review of certain values and, even more, certain faults of today’s world with the aim of comparing the modernized world to patriarchate, which was extensively written about by Svetozar Marković in Serbia in the East. Unlike today’s dominant trend to disrespect the patriarchal way of life and to ignore its values, Svetozar wrote a special praise to patriarchate, but also expressed his regret because Serbian society, after the liberation from the Turkish rule and the establishment of its own state, was not built on its patriarchal foundations, but became bureaucratized following some Western models even after the West itself had abandoned them. He thought that Serbia’s place was in the East, among Slavic nations and states, whose social foundations were also patriarchal. However, historical trends, contrary to Marković’s expectations, proceeded mostly in an opposite direction. The paper is aimed at juxtaposing two worlds, the patriarchal one, as testified by Svetozar Marković in his most important book, and the modern one, as seen in the literature and the author’s direct empirical insight. The analysis will apply the historical approach and the comparative method.